Multiple roles of COUP-TFII in cancer initiation and progression - Litchfield, Lacey M. (2012)
COUP-TFII is an orphan nuclear receptor that acts as a transcriptional activator or repressor in a cell type-dependent manner. Best characterized for its role in the regulation of angiogenesis during mouse development, COUP-TFII also plays important roles in glucose metabolism and cancer. Expression of COUP-TFII is altered in various endocrine conditions. Cell type-specific functions and the regulation of COUP-TFII expression result in its varying physiological and pathological actions in diverse systems. Evidence will be reviewed for oncogenic and tumor suppressive functions of COUP-TFII, with roles in angiogenesis, metastasis, steroidogenesis, and endocrine sensitivity of breast cancer described. The applicability of current data to our understanding of the role of COUP-TFII in cancer will be discussed.